2015
DOI: 10.1021/nn505634h
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid-Dependent Attenuation of Toll-like Receptor Signaling by Peptide-Gold Nanoparticle Hybrids

Abstract: Manipulation of immune responsiveness using nanodevices provides a potential approach to treat human diseases. Toll-like receptor (TLR) signaling plays a central role in the pathophysiology of many acute and chronic human inflammatory diseases, and pharmacological regulation of TLR responses is anticipated to be beneficial in many of these inflammatory conditions. Here we describe the discovery of a unique class of peptide-gold nanoparticle hybrids that exhibit a broad inhibitory activity on TLR signaling, inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 31 publications
1
83
0
1
Order By: Relevance
“…One exciting invention is the development of a completely novel peptide-GNP hybrid system as a next generation nano-inhibitor led by Yang et al (2015, 2016). The system is made of a GNP core coated with a hexapeptide layer to enhance the physiological stability of the GNP, change the surface physicochemical characteristics, and enable the biological activity (Yang et al, 2011, 2013).…”
Section: Toll-like Receptor Antagonists/inhibitors and Their Clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…One exciting invention is the development of a completely novel peptide-GNP hybrid system as a next generation nano-inhibitor led by Yang et al (2015, 2016). The system is made of a GNP core coated with a hexapeptide layer to enhance the physiological stability of the GNP, change the surface physicochemical characteristics, and enable the biological activity (Yang et al, 2011, 2013).…”
Section: Toll-like Receptor Antagonists/inhibitors and Their Clinicalmentioning
confidence: 99%
“…Through, screening a small library of the established, physiologically stable peptide-GNP hybrids, they discovered a potent multi-TLRs inhibitor, P12, which not only suppressed both arms of TLR4 signaling (i.e., MyD88-dependent NF-κB and TRIF-dependent IRF3 activation), but also inhibited TLR2, TLR3, and TLR5 pathways. The structure-activity relationship analysis revealed that the activity index is strongly dependent on the surface properties of the hybrid, where the hydrophobicity and the aromatic ring-like structure are the two key factors dictating the inhibitory activity (Yang et al, 2015). Further studies conferred the anti-inflammatory activity of P12 in correcting LPS-induced gene expressions, reducing the subsequent pro-inflammatory cytokine production (IL-12p40, MCP-1, and IFN-γ), and increasing the anti-inflammatory cytokine IL-1RA.…”
Section: Toll-like Receptor Antagonists/inhibitors and Their Clinicalmentioning
confidence: 99%
“…The coating peptides are rationally designed to stabilize GNPs in physiological conditions and to manipulate both their cellular uptake and immune responses. Through high‐throughput screening, we identified a group of hybrids that were capable of inhibiting multiple TLR pathways in human mononuclear immune cells (including macrophages) in vitro . Among them, the lead nanoparticle hybrid (designated P12) showed potent inhibitory activity on the signaling of TLRs 2, 3, 4 and 5, as well as the downstream proinflammatory cytokine production .…”
Section: Introductionmentioning
confidence: 99%
“…As described in Section , recent studies have demonstrated that biomaterials display intrinsic properties that can drive inflammatory or proimmune function in immune cells. Other recent studies have described tolerogenic properties of various biomaterials, including synthetic polymers such as PLGA and PS, QDs, gold NPs, and cellulose nanofibers . These intrinsic biomaterial properties are now starting to be explored in therapeutic contexts as tools to promote tolerance in preclinical models of autoimmune disease.…”
Section: Biomaterials Display Intrinsic Immunogenic Materials Propertimentioning
confidence: 99%